2021
DOI: 10.1038/s41598-021-03577-1
|View full text |Cite
|
Sign up to set email alerts
|

Network oscillations imply the highest cognitive workload and lowest cognitive control during idea generation in open-ended creation tasks

Abstract: Design is a ubiquitous, complex, and open-ended creation behaviour that triggers creativity. The brain dynamics underlying design is unclear, since a design process consists of many basic cognitive behaviours, such as problem understanding, idea generation, idea analysis, idea evaluation, and idea evolution. In this present study, we simulated the design process in a loosely controlled setting, aiming to quantify the design-related cognitive workload and control, identify EEG-defined large-scale brain networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 104 publications
(121 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, information-theoretical analysis of microstate sequences during a design task has shown that the entropy rate (von Wegner et al 2018) and oscillatory microstate dynamics are modulated by cognitive tasks, and that these metrics indicate the balance between cognitive workload and cognitive control (Jia et al 2021). Yet, we do not know how whether this interpretation is compatible with our understanding of reduced cognition during sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, information-theoretical analysis of microstate sequences during a design task has shown that the entropy rate (von Wegner et al 2018) and oscillatory microstate dynamics are modulated by cognitive tasks, and that these metrics indicate the balance between cognitive workload and cognitive control (Jia et al 2021). Yet, we do not know how whether this interpretation is compatible with our understanding of reduced cognition during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…This observation, together with the lower microstate entropy rate, speak for a more restricted, and therefore more predictable trajectory of the underlying neuronal ensembles in deeper sleep stages. During complex cognitive tasks, the largest microstate entropy rates have been observed in subtasks with the highest cognitive workload and the lowest degree of cognitive control(Jia et al 2021). The current results extend these observations while pointing in the same direction, as they suggest a further decrease in cognitive workload with deepening sleep.…”
mentioning
confidence: 99%
“…Although the aim of the authors was to address self-similarity and fractality rather than explicitly measuring complexity, the relationship between Hurst exponents and complex systems properties is present throughout the article. We evaluated their approach in relation to Markov models of microstate sequences in (von Wegner et al, 2016) and applied it to cognitive load assessment in (Jia et al, 2021).…”
Section: Complexity and Microstate Researchmentioning
confidence: 99%
“…Entropy rate estimation for microstate sequence analysis was introduced in (von Wegner et al, 2018a), and we evaluated its changes during different types of cognitive effort in (Jia et al, 2021), and for NREM sleep stages in (Wiemers et al, 2022). We interpreted entropy rate in terms of sequence predictability in (von Wegner et al, 2018a) and (Jia et al, 2021), and as a complexity measure in (Wiemers et al, 2022).…”
Section: Complexity and Microstate Researchmentioning
confidence: 99%
“…The EEG data processing was conducted in MATLAB ® using the EEGLAB toolbox 53 . An original script for data processing was developed according to the pipelines described by Li et al 54 , Vieira et al 28 , and Jia et al 55 . In the rst step, DC offset speci c for Emotiv EPOC + devices was removed with the in nite impulse response (IIR) lter.…”
Section: Data Pre-processingmentioning
confidence: 99%